THE LEGAL VALUE OF SYSTEMATIZATION IN THE CONTEXT OF E-GOVERNANCE - Danielyan, Gevorg (State and Law, 2025)
In the article theoretical and legal aspects of the method of coordination, objectively necessary from the point of view of modern peculiarities of management, but ignored in practice, are investigated from modern scientific and practical aspects. At the same time it is concluded that coordination is seen as a kind of indicator of the degree of democratization of governance and emphasizes that coordination is being squeezed out of public life, especially when not only in the executive branch but also in other branches of government, single-person management becomes dominant through the consolidation of key functions of bodies.Basically, it is about a method of management that has hardly become a subject of research and is still out of sight of researchers, while it has a clear modern meaning. Accordingly, in the article, the real reasons of the said paradoxical situation were comprehensively examined.This study has highlighted the basis for the application of the term "coordination" in several meanings and the specific content of each of them. The final part of the article summarizes the features of individual types of coordination and the general features of coordination.The article presents as concisely as possible the most effective organizational vectors for further improvement of legal, theoretical and practical bases of coordination, overcoming obstacles to the application of this method.
Keywords: Constitution; coordinating power; management method; executive power; principle; harmony; consensus; effectiveness of management